Measuring the Nonmonetary Component of General Value for Goods and Services - Aityan, Sergey K.; Ivanov-Schitz, Alexey K.; Logunova, Eugenia (International Journal of Economics and Financial Issues, 2017)
The recently introduced theory of general value addresses two distinct components of value: monetary and nonmonetary. The introduction of the nonmonetary component of value helps explain many types of decisions and choices, which were not clearly understood before, and helps with the strategic planning and actions. This paper introduces a methodology of measuring nonmonetary value of goods and services in the perception of people. The indifference point between two choices is used to measure the difference of nonmonetary components in terms of the difference of the monetary components with the opposite sign. This method was used to measure relative nonmonetary values (the difference of the monetary components) of various goods and services in the perception of different social groups. Keywords: value, nonmonetary, utility, preference, behavioral economics, decision-making, personal choice Classifications: A130, D01, D03